Roles, Challenges, and Solutions in Dealing with School Administration Management - Ningrum, Gusti Puspita; Kusumaningrum, Desi Eri; Sumarsono, Raden Bambang (Proceedings Series of Educational Studies, 2024)
The management of school administration personnel is one of the important elements in supporting the smooth operation of schools. Administrative roles are not only limited to technical tasks such as data management, finance, and logistics, but also function in supporting the teaching and learning process. This article aims to analyze the roles, challenges, and solutions in the management of school administration personnel in Indonesia using the literature review method from research from 2019 to 2024. The findings of the study show that technology, continuous training, and organizational restructuring are important solutions in overcoming the challenges faced by school administrators. This research also suggests increasing the role of administrative personnel in supporting the quality of education through innovation and digitalization